2007
DOI: 10.21091/mppa.2007.2013
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the Violin–Performer Interface: An Experimental Study about the Effects of Shoulder Rest Variations on Playing Kinematics

Abstract: Playing a musical instrument is a constrained motor activity; the instrument has a fixed geometry and playing technique that the performer must accommodate. Although the performer progressively adapts to the instrument during years of education, few options are available for adapting the instrument to the performer. The present work is intended to quantitatively describe the effects of using different setups of the violin shoulder rest during performance. Three conditions were considered, the maximum and mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Fry, 1986;Fishbein and Middlestadt, 1988;Middlestadt and Fisbein, 1989;Schuppert and Altenmüller, 1999;Liu and Hayden, 2002;Sakai, 2002;Rosety-Rodriguez et al, 2003;Moraes and Papini, 2012;Paarup et al, 2012; Ackermann et al, 2002;de Greef et al, 2003;Barton and Feinberg, 2008;Chan et al, 2013aLópez and Martínez, 2013;McCrary et al, 2016 Manual therapy, therapeutic exercises, education and advice (e.g., about performance posture, practice habits, possible injury risks etc. ), music performance biomechanics feedback, ergonomic considerations Ackermann et al, 2002;de Greef et al, 2003;Shafer-Crane, 2006;Rabuffetti et al, 2007;Barton and Feinberg, 2008;Chan et al, 2013b;López and Martínez, 2013;McCrary et al, 2016 Mobility dysfunction Fishbein and Middlestadt, 1988;Middlestadt and Fisbein, 1989;Larsson et al, 1993;Gannon and Bird, 1999;Schuppert and Altenmüller, 1999;Brandfonbrener, 2002;Liu and Hayden, 2002;Sakai, 2002;Day et al, 2011;Driscoll and Ackermann, 2012;Paarup et al, 2012;Artigues-Cano, 2014;Skwiot et al, 2019…”
Section: Methods the Physiotherapeutic Consulting Hoursmentioning
confidence: 99%
“…Fry, 1986;Fishbein and Middlestadt, 1988;Middlestadt and Fisbein, 1989;Schuppert and Altenmüller, 1999;Liu and Hayden, 2002;Sakai, 2002;Rosety-Rodriguez et al, 2003;Moraes and Papini, 2012;Paarup et al, 2012; Ackermann et al, 2002;de Greef et al, 2003;Barton and Feinberg, 2008;Chan et al, 2013aLópez and Martínez, 2013;McCrary et al, 2016 Manual therapy, therapeutic exercises, education and advice (e.g., about performance posture, practice habits, possible injury risks etc. ), music performance biomechanics feedback, ergonomic considerations Ackermann et al, 2002;de Greef et al, 2003;Shafer-Crane, 2006;Rabuffetti et al, 2007;Barton and Feinberg, 2008;Chan et al, 2013b;López and Martínez, 2013;McCrary et al, 2016 Mobility dysfunction Fishbein and Middlestadt, 1988;Middlestadt and Fisbein, 1989;Larsson et al, 1993;Gannon and Bird, 1999;Schuppert and Altenmüller, 1999;Brandfonbrener, 2002;Liu and Hayden, 2002;Sakai, 2002;Day et al, 2011;Driscoll and Ackermann, 2012;Paarup et al, 2012;Artigues-Cano, 2014;Skwiot et al, 2019…”
Section: Methods the Physiotherapeutic Consulting Hoursmentioning
confidence: 99%
“…Maintenance of musical performance despite different instrumental setups had already been observed with the introduction of shoulder rests—which elevate the violin (Rabuffetti et al, 2007). Indeed, Rabuffetti et al (2007) found that expert violinists could play scales with no and different heights of shoulder rests, without affecting sound quality (Rabuffetti et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The scientific basis for a better understanding of ergonomics in violin playing and teaching is gaining grounds ( Szende and Nemessury, 1971 ; Ackerman and Adams, 2004 ; Wagner, 2005 ; Wagner, 2012 ; Rensing et al, 2018 ; Chi et al, 2020 ), but co-exists with a wide and contradictory spectrum of long-standing teaching and performing traditions ( Flesch, 1978 ; Galamian, 1983 ; Rostal, 1993 ; Rônez-Kubitschek, 2012 ). Gaining insight into the use of the left upper extremity when playing the violin is a research topic often contributed to in recent years ( Blum, 1995a , b ; Zaza, 1998 ; Künzel, 2000 ; Ackermann and Adams, 2003 ; Shan and Visentin, 2003 ; Nyman et al, 2007 ; Rabuffetti et al, 2007 ; Wahlström and Fjellman-Wiklund, 2009 ; Obata and Kinoshita, 2012 ; Lee et al, 2013 ; Reynolds et al, 2014 ; Möller et al, 2018 ). Nevertheless, only few studies focusing on individual physical predispositions concerning the instrument could be identified ( Ackermann and Roger, 2003 ; Steinmetz et al, 2006 ; Storm, 2006 ; Rabuffetti et al, 2007 ; Seidel et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gaining insight into the use of the left upper extremity when playing the violin is a research topic often contributed to in recent years ( Blum, 1995a , b ; Zaza, 1998 ; Künzel, 2000 ; Ackermann and Adams, 2003 ; Shan and Visentin, 2003 ; Nyman et al, 2007 ; Rabuffetti et al, 2007 ; Wahlström and Fjellman-Wiklund, 2009 ; Obata and Kinoshita, 2012 ; Lee et al, 2013 ; Reynolds et al, 2014 ; Möller et al, 2018 ). Nevertheless, only few studies focusing on individual physical predispositions concerning the instrument could be identified ( Ackermann and Roger, 2003 ; Steinmetz et al, 2006 ; Storm, 2006 ; Rabuffetti et al, 2007 ; Seidel et al, 2009 ). The number of studies dedicated to electromyographic (EMG) measurements of violinists is growing.…”
Section: Introductionmentioning
confidence: 99%